The Effect of Pick-Up Service on Customer Satisfaction at PT Bank BRI Airmadidi Sub-Branch - Maliangkay, Michela (JURNAL ADMINISTRASI BISNIS, 2025)
This research investigates how the Pick-Up Service influences customer satisfaction at PT Bank BRI KCP Airmadidi. Employing a quantitative method and a saturated sampling technique, the study involved 30 participants. Data were obtained via questionnaires and analyzed using simple linear regression with SPSS software. The analysis revealed a statistically significant positive relationship between the Pick-Up Service and customer satisfaction, supported by a significance level of 0.000, which is below the 0.05 threshold. The results highlight the critical roles of punctuality, clear communication, and professional staff conduct in delivering satisfactory service. The study recommends enhancing employee training and improving service scheduling to sustain and elevate customer satisfaction levels.